Product Development using QFD, MCDM and the Combination of these Two Methods - Marini, C. D.; Fatchurrohman, Nanang; Azmir, Azhari; Suraya, Sulaiman (IOP Publishing, 2016)

(untitled)
Product development (PD) consists of several activities and one of early stage in PD is conceptual design stage which is the most crucial stage in developing a new product. Incorrect design concept and material selection in conceptual stage will lead to product failure and increase the cost. Nevertheless, if the conceptual design stage is properly executed important parameters such as the time and cost can be minimized. The quality of the product also has a tremendous improvement. This paper mainly discuss on tooling medium used for material selection and design concept. It covers Quality Function Deployment (QFD), Multi Criteria Decision Making (MCDM) including Analytical Network Process (ANP) and Analytical Hierarchy Process (AHP).